Proteksi Konsleting Listrik Dengan Memutus Jarak Jauh Arus 3 Phasa Beban Besar Dengan Kombinasi Solid State Relay (SSR) dan IoT NodeMCU 8266 Menggunakan Aplikasi Blynk di Sub Panel Gedung Telkomsel Smart Office Renon Denpasar - Hardiansyah, Amien Harist; Hartati, Rukmi Sari; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro; Vol 22 No 1 (2023): (Januari - Juni) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i01.P09, 2023)
70% of building fires in Indonesia are caused by electrical short circuits, the rest are caused by other things such as negligence and also gas. Electrical short circuits contribute to the biggest problem in cases of building fires in Indonesia due to concern for maintenance and checking which is often missed due to problems with routine and periodic checking schedules that are not monitored in a lifetime or continuously. One of the methods used to overcome this problem is to continuously monitor the measurement values on the electrical sub-panels in real time. Manual checking is no longer effective due to electrical problems. One minute ago we checked and we can conclude that the panel is in good condition and safe. Because electricity can suddenly have problems without us realizing it and it really needs to be handled extra quickly to take action to cut off the power lines so that short circuits or hot copper sections do not occur which can cause panel fires and can also cause building fires. With today's increasingly sophisticated digital technology, we can innovate by implementing IoT (Internet Of Thing) using the Bynk Android Application as a remote control for monitoring load values and also being able to trigger 3-phase power lines using only a smartphone anywhere as long as the internet is connected so that when If there is an electrical problem with the sub panel inside the building, it will be handled/disconnected immediately. From the research results obtained, the Solid State Relay component can be combined with a microcontroller as the main control line to cut off large electric currents, where the microcontroller uses a 5 Volt input control and SSR (Solid State Relay) uses a 3 Volt - 32 Volt output so that it can be modified and can cut off and monitor traffic only with a smartphone using the Blynk Application. Keyword—Aplication Blynk; short circuits; Protection; SSR (Solid State Relay)